Climate change impacts on groundwater resources in Mekong Delta under representative concentration pathways (RCPs) scenarios. Issue 61 (July 2016) - Shrestha, Sangam; Bach, Tran Viet; Pandey, Vishnu Prasad
Graphical abstract: Highlights: A set of models (i.e., WETSPASS, MODFLOW & GCMs under RCP scenarios) are used. Average annual temperature is projected to increase by 1.5 °C and 4.9 °C by the end of the 21st century under RCP4.5 and RCP8.5 scenarios, respectively. Future rainfall is projected to increase in wet season and decrease in dry season. Groundwater recharge is projected to decline in short-, medium-, and long-terms. Groundwater levels and storage are also projected to decline in future. Abstract: Groundwater is the essential resource for various uses and have a great economic importance especially in the areas like Mekong Delta, which is the home for some 18 million people and produces a half of Vietnam's rice and contributes substantial part of the country's gross domestic product (GDP). Sustainable use of the groundwater resource is threatened by its uncontrolled abstraction and climate change. This study assesses groundwater resources in Mekong Delta aquifer system in the context of climate change. A set of models are used for the purpose. Groundwater recharge and its spatial variation are estimated using WETSPASS model, groundwater level and storage are estimated using MODFLOW and future climatic conditions in the area are developed by downscaling the data of five General Circulation Models (GCMs) retrieved from CMIP5 data portal. Two representative concentration pathways (RCPs) scenarios (RCP4.5 and RCP8.5) are considered for projecting future conditions of groundwater resources. Results reveal that the future average annual temperature is projected to increase by 1.5 °C and 4.9 °C by the end of the 21st century under RCP4.5 and RCP8.5 scenarios, respectively. Future rainfall is projected to increase in wet season and decrease in dry season. Groundwater recharge is projected to decline in short-, medium-, and long-terms. As a result, groundwater levels and storage are also projected to decline in future. These findings may help decision-makers and stakeholders for devising sustainable groundwater management strategies in Mekong Delta.